Politeness Strategies in a Princess Tale: A Pragmatic Analysis of Barbie and the Diamond Castle - Pande Komang Dewi Utari; Putu Gede Budiartha (Universitas Islam Negeri Palopo, 2025)
This study investigates the politeness strategies employed by characters in the animated film Barbie and the Diamond Castle, aiming to explore how these strategies function to maintain social harmony and manage interpersonal relationships. The research is grounded in Brown and Levinson’s (1987) politeness theory, which categorizes politeness strategies into four types: bald on-record, positive politeness, negative politeness, and off-record. A total of 30 utterances containing politeness strategies were carefully extracted from the film’s dialogues through repeated viewings and transcription. Using a qualitative descriptive approach, the analysis revealed that positive politeness was the most frequently employed strategy, occurring 12 times (40,00%), followed by bald on-record strategies with 10 occurrences (33,33%). Negative politeness and off-record strategies were observed less frequently, with 4 (13.33%) and 4 (13.33%) occurrences, respectively. These findings suggest that the characters predominantly use positive politeness to convey friendliness and foster solidarity, while bald on-record strategies mainly serve direct and urgent communicative functions. Despite their lower frequency, negative politeness and off-record strategies play crucial roles in mitigating face-threatening acts and enriching subtlety in interpersonal interaction. This study addresses a significant gap in pragmatic research concerning politeness in children’s animated media, which remains underexplored compared to adult-oriented content. The results offer valuable implications for educators, linguists, and media producers aiming to enhance socially appropriate communication in children’s programming.